Assessment of iron deficiency anaemia and its risk factors among adults with chronic kidney disease in a tertiary hospital in Nigeria (2021)
A substantial proportion of patients with chronic kidney disease (CKD) develop iron deficiency anaemia (IDA). Despite the association of IDA with adverse cardiovascular outcomes, it remains underdiagnosed and poorly managed. Up to 70% of patients with CKD are anaemic at the time of initiating dialysis, while the predictors of IDA in these patients in our setting are unknown. This study aimed to determine the prevalence and risk factors for IDA in patients with CKD. Materials and Methods: This is a case–control study of 157 patients with CKD and 157 age and gender matched subjects without CKD. Information obtained from the participants were socio demographic details, aetiology of CKD, medication history and features of IDA. All participants had serum ferritin, total iron binding capacity (TIBC), transferrin saturation (TSAT), highly sensitive C reactive protein, serum creatinine and complete blood count determined. Results: The median estimated glomerular rate (22.7 [3.4–59.5] vs. 110.2 [60.3–152.8] ml/min/1.73 m2 , P < 0.01), the mean haemoglobin concentration (9.3 ± 2.6 vs. 11.4 ± 1.7 g/dl, P < 0.01), and TSAT (27.9% ± 6.4% vs. 34.8% ± 8.1%, P < 0.04) were significantly lower in patients with CKD. The mean age, serum ferritin and TIBC were similar in both groups. The prevalence of absolute (24.8% vs. 13.4%, P < 0.01) and relative (17.8% vs. 7.6%, P < 0.01) iron deficiencies were higher among individuals with CKD compared to the controls. Female gender (odd ratio [OR]:1.50, 95% confidence interval [CI]:1.0267–4.1163, P < 0.04) and severity of CKD (OR: 3.43, 95% CI: 1.5568–7.8324, P < 0.02) were independently associated with IDA. Conclusion: IDA is common among individuals with CKD while female gender and severity of CKD were factors that independently predicted IDA